2019
DOI: 10.1088/1361-6633/ab4fc5
|View full text |Cite
|
Sign up to set email alerts
|

Strong gravitational lensing of explosive transients

Abstract: Recent rapid progress in time domain surveys makes it possible to detect various types of explosive transients in the Universe in large numbers, some of which will be gravitationally lensed into multiple images. Although a large number of strongly lensed distant galaxies and quasars have already been discovered, strong lensing of explosive transients opens up new applications, including improved measurements of cosmological parameters, powerful probes of small scale structure of the Universe, and new observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
143
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 429 publications
2
143
0
2
Order By: Relevance
“…For a given observed GW signal, the luminosity distance to the source, and thus its redshift, may then be much larger than in the absence of lensing. Strong lensing is expected to be relatively rare at current detector sensitivities, with 1 in every 100-1000 detected events strongly lensed by individual galaxies (Holz & Wald 1998;Li et al 2018;Ng et al 2018;Oguri 2018) and a similarly low rate for lensing by galaxy clusters (Smith et al 2018;Oguri 2019).…”
Section: Strong Gravitational Lensingmentioning
confidence: 99%
“…For a given observed GW signal, the luminosity distance to the source, and thus its redshift, may then be much larger than in the absence of lensing. Strong lensing is expected to be relatively rare at current detector sensitivities, with 1 in every 100-1000 detected events strongly lensed by individual galaxies (Holz & Wald 1998;Li et al 2018;Ng et al 2018;Oguri 2018) and a similarly low rate for lensing by galaxy clusters (Smith et al 2018;Oguri 2019).…”
Section: Strong Gravitational Lensingmentioning
confidence: 99%
“…One example of such an avenue is gravitationally lensed GWs, the first of which may be possible to observe in the next few years (Ng et al 2018;Li et al 2018;Oguri 2018). It has been suggested that lensed GWs might offer interesting applications in fundamental physics, astrophysics, and cosmology (Sereno et al 2011;Liao et al 2017;Collett & Bacon 2017;Fan et al 2017;Baker & Trodden 2017;Lai et al 2018;Dai et al 2018;Mukherjee et al 2019;Oguri 2019;Pang et al 2020;Jung & Shin 2019;Cao et al 2019;Hou et al 2020;Sun & Fan 2019;Hannuksela et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore useful and customary to identify several regimes of lensing depending on the particular configuration of the system at hand (Dodelson 2017;Schneider et al 1992). The case in which multiple images and arcs are produced is known as strong lensing (Oguri 2019;Treu 2010), whereas the less dramatic-but much more common-case, in which the lensing signal is so subtle that it can only be detected statistically, is known as weak lensing (Bartelmann and Maturi 2017;Schneider 2005;Bartelmann and Schneider 2001). A third regime known as microlensing uses the magnification of the image of a source star when it is aligned with another lensing star along the line of sight.…”
Section: Introductionmentioning
confidence: 99%